Improving Grade V Students’ Indonesian Language Learning Outcomes through Unplugged Media and the Information for Investigation Method: A Classroom Action Research on Synonyms and Antonyms - Aji dwi nugraha; Mareta silaturi; Ana swita; Dessy Wardiah; Eni Heldayani (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to improve Indonesian language learning outcomes of fifth-grade students at SD Negeri 85 Palembang on the topic of synonyms and antonyms by implementing unplaged media for 21st-century learning and applying the information for investigation method. The study employed a classroom action research (car) design carried out in several cycles, including planning, implementing the action, observing, and reflecting. The participants were 28 fifth-grade students. Data were collected through learning achievement tests, observations of students' and teachers' activities, and documentation. Data analysis was conducted quantitatively for test scores and qualitatively for learning activities. The findings indicate that the use of unplaged media combined with the information for investigation method effectively enhances students' learning outcomes. Mastery learning increases from cycle to cycle, reflected in the rise of the average scores and the proportion of students who meet the minimum mastery criterion (KKTP). In addition, students' learning activities also improved, including greater participation in discussions, improved ability to gather information from learning materials, and increased confidence in presenting investigation results. Therefore, the study concludes that applying un plaged media in 21st-century learning with the information for investigation method is effective for improving Indonesian language learning outcomes on synonyms and antonyms for fifth-grade students at SD Negeri 85 Palembang